Penerapan Instruksi pada Tahap Orientation Pembelajaran Discovery untuk Meningkatkan Kemampuan Menemukan dan Menghubungkan Konsep - Galuh Yuli Nurastuti; Joko Ariyanto; Sri Widoretno (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The aim of the research is to improve the abilities of finding and correlating the concept by applicate the instruction of the orientation stage of discovery learning. The research is action class research with 2 cycles. The procedures are planning, implementation, observation and reflection. The subjects of the research are high school students that consist of 10 men and 25 women. The datas of research are the answers and students' note, and also the score of concept map based on expert concept map. The collection of the datas are using observation, interview, documentation and examination to measure the score of the concept map. The validity test is by triangulation technique method. The analyses of the data are by the data reduction, data presentation, and concluding process. The result of the research shows the score the students' ability to find and correlate the concept, measured by using concept map based on the expert concept map. The results of the pre-cycle are on the range 2,84%-18,04%, which the average score of the concept map on the pre-cycle is 9,12% with 16 students are above average. The first cycle has score range between 5,76%-46,3%, which the average score of the concept map is 22,75% with 14 students above average. The second cycle has score range between 5,00%-45,15% which the average score of the concept map is 26,52% with 18 students above average. Thus the implementation of the orientation stage of discovery learning improve the abilities of finding and correlating the concept, measured by the score of the concept map on the first and second cycle.